Mendiagnosis Gugus Konsonan dalam Bahasa Gorontalo: Revitalisasi Bahasa Daerah di Kawasan Teluk Tomini - Dako, Rahman Taufiqrianto; Malik, Harto S.; Djou, Dakia N. (Al-Lisan: Jurnal Bahasa, 2025)
Background: The term "diagnosis" is used in this study to reflect the careful and systematic approach needed to investigate the phonological features of Gorontalo Language (GL). This research study investigates the consonant clusters of the GL covering the phonetic, phonological, and phonotactic approaches focusing on the sounds of /mb/, /nt/, and /ngg/. Aims: The research aims to clarify whether these sounds are single consonant or consonant clusters, contributing to both linguistic theory and the revitalization efforts for the GL in the Tomini Bay region. Methods: The qualitative methodology utilized in this research is an analytical method associated with simultaneous data collection and analysis. The study assesses the phonological characteristics of GL with an emphasis on consonant clusters using a thorough literature analysis and real-world sources, including social media and interviews. A comprehensive description of GL's sound system can be obtained by applying phonetical, phonological, and phonotactical analyses of sound, phoneme, and syllable structures. Results: Based on Gorontalo's phonetics, phonology, and phonotactics rules, the sounds /mb/, /nt/, and /ngg/ function as consonant clusters rather than a single consonant. Each sound in /mb/, /nt/, and /ngg/ is created uniquely, according to phonetic, phonological, and phonotactical analysis verifies that they function as independent phonemes that alter the meaning of words. Additionally, their classification as consonant clusters rather than a single consonant is supported by Gorontalo's phonotactic rules, which forbid consonants at syllable endings. Implications: These clusters can find utility within educational resources, thereby reinforcing linguistic sustainability. This work contributes not only to linguistic knowledge regarding Gorontalo phonetical, phonological, and phonotactic but also has applications to inform the design of revitalization programs for endangered languages.